2020
DOI: 10.3390/agronomy10091269
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Different Crop Rotation Schemes for Organic Common Bean Production

Abstract: The aim of the current study was to contribute to the establishment of sustainable organic crop rotation schemes for common bean under mild-winter climatic conditions. Common bean was cultivated according to organic or conventional farming practices during spring-summer in two successive years with crop and treatment during the preceding winter as either: (a) organic broccoli, (b) conventional broccoli, (c) organic faba bean used as green manure, or (d) fallow. Common bean was either inoculated with Rhizobium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…An additional reason is that the BNF efficiency of faba bean is not particularly affected by the level of inorganic N in the soil, presumably because this plant has a relatively low efficiency to exploit the soil N [ 25 , 26 , 28 ]. Furthermore, the N 2 fixation efficiency of common bean is generally lower than that of other legumes, according to several studies [ 21 , 23 , 26 ]. The present study confirmed the lower N 2 fixation efficiency of common bean as the %Ndfa in this legume was appreciably lower than that found in cowpea and faba bean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional reason is that the BNF efficiency of faba bean is not particularly affected by the level of inorganic N in the soil, presumably because this plant has a relatively low efficiency to exploit the soil N [ 25 , 26 , 28 ]. Furthermore, the N 2 fixation efficiency of common bean is generally lower than that of other legumes, according to several studies [ 21 , 23 , 26 ]. The present study confirmed the lower N 2 fixation efficiency of common bean as the %Ndfa in this legume was appreciably lower than that found in cowpea and faba bean.…”
Section: Discussionmentioning
confidence: 99%
“…Crop rotations are the cornerstone of organic farming systems, as they contribute crucially to both maintenance of soil fertility [ 21 ], and control of pests, diseases and weeds [ 22 ]. Therefore, many scientists have proposed the reintroduction of legumes into the crop rotation systems, as they act as N fertilization sources for the next crop.…”
Section: Introductionmentioning
confidence: 99%
“…Similar reports concerning the relation between inorganic-N input and C:N ratio were also found in the study by Kontopoulou et al [ 56 ], in which the limited N-availability in an organic common-bean crop increased the shoot C:N ratio compared to that found in plants grown conventionally. In contrast, Karavidas et al [ 57 ] found that although the organic farming practices restricted the soil N availability, the N content and the C:N ratio in common bean shoots were not influenced. This discrepancy was presumably because the shortage of soil N in the study by Karavidas et al [ 57 ] was less restrictive than those of the current study, and those of Kontopoulou et al [ 56 ].…”
Section: Discussionmentioning
confidence: 95%
“…While the classic method of legume-based green manuring in the field offers only N and also provides some benefits with respect to phosphorus (P) availability, MGM enriches the soil with all of the macronutrients and trace elements that are necessary for plant growth. On the other hand, part of the benefit of legume crop rotation is due to the improvement of the soil properties and the reduction of plant pathogens [10,11,26]. This benefit is lost when MGM is applied.…”
Section: Introductionmentioning
confidence: 99%